Sovereign women in a Muslim kingdom the sultanahs of Aceh, 1641-1699 - Khan, Sher Banu A. L. (NUS Press, 2017)
The Islamic kingdom of Aceh was ruled by queens for half of the 17th century. Was female rule an aberration? Unnatural? Indigenous texts and European sources offer different evaluations. Drawing on both sets of sources, this book shows that female rule was legitimised both by Islam and indigenous customary laws, and provides original insights on the Sultanah's leadership.